Palazzo Querini Stampalia, Situationsmodell - (:unkn) unknown (Chalmers tekniska högskola // Institutionen för arkitektur och samhällsbyggnadsteknik, 2022)
Carlo Scarpa is the architect behind the modern renovation of the garden and part of the ground floor for the Venetian institution Querini Stampalia. Scarpa is admired for his balanced combination of old and new elements, as well as on a great workmanship of the materials. The model represents the context of the building. It shows the relation to Venice's canals, squares, streets and surrounding houses. By placing the model on a twirling plate, the spectator is able to easily see into all narrow alleys between the buildings. The massive buildings are significant to the experience of the location, hence, mdf was a suitable material to illustrate in. The brown 12mm-thick discs symbolize floors on a scale of 1:300.
Palazzo Querini Stampalia model